(untitled) (Global Journal of Management and Business Research, 2022)
Customer preference is ever changing yet it is very integral in hospitality industry. Understanding the factors that affect the customer choices between Fine Dining Restaurant and Quick Service Restaurant is important. This study will help to analyze whether customers prefer HotelCrowne Plaza Greater Noida, which is a five-star hotel that offers Fine dining for its guests in the various restaurants, Mosaic multi-cuisine coffee shop, Spice Art- Indian restaurant, ChaoBella - offering Korean food to it#x2019;s in house guests, or they prefer to dine in Quick Service Restaurant within Greater Noida and Delhi